High Interobserver Agreement for the Standardized Reporting System SSTR-RADS 1.0 on Somatostatin Receptor PET/CT - Werner, Rudolf A. (J Nucl Med, 2021)
Recently, a standardized framework system for interpreting somatostatin receptor (SSTR)–targeted PET/CT, termed the SSTR reporting and data system (RADS) 1.0, was introduced, providing reliable standards and criteria for SSTR-targeted imaging. We determined the interobserver reliability of SSTR-RADS for interpretation of (68)Ga-DOTATOC PET/CT scans in a multicentric, randomized setting. Methods: A set of 51 randomized (68)Ga-DOTATOC PET/CT scans was independently assessed by 4 masked readers with different levels of experience (2 experienced readers and 2 inexperienced readers) trained on the SSTR-RADS 1.0 criteria (based on a 5-point scale from 1 [definitively benign] to 5 [high certainty that neuroendocrine neoplasia is present]). For each scan, SSTR-RADS scores were assigned to a maximum of 5 target lesions (TLs). An overall scan impression based on SSTR-RADS was indicated, and interobserver agreement rates on a TL-based, on an organ-based, and on an overall SSTR-RADS score–based level were computed. The readers were also asked to decide whether peptide receptor radionuclide therapy (PRRT) should be considered on the basis of the assigned RADS scores. Results: Among the selected TLs, 153 were chosen by at least 2 readers (all 4 readers selected the same TLs in 58 of 153 [37.9%] instances). The interobserver agreement for SSTR-RADS scoring among identical TLs was good (intraclass correlation coefficient [ICC] ≥ 0.73 for 4, 3, and 2 identical TLs). For lymph node and liver lesions, excellent interobserver agreement rates were derived (ICC, 0.91 and 0.77, respectively). Moreover, the interobserver agreement for an overall scan impression based on SSTR-RADS was excellent (ICC, 0.88). The SSTR-RADS–based decision to use PRRT also demonstrated excellent agreement, with an ICC of 0.80. No significant differences between experienced and inexperienced readers for an overall scan impression and TL-based SSTR-RADS scoring were observed (P ≥ 0.18), thereby suggesting that SSTR-RADS seems to be readily applicable even for less experienced readers. Conclusion: SSTR-RADS–guided assessment demonstrated a high concordance rate, even among readers with different levels of experience, supporting the adoption of SSTR-RADS for trials, clinical routine, or outcome studies.